2019
DOI: 10.3390/ma12213585
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Polymer-Supported N-Hydroxyphthalimide Catalysts for Selective Oxidation of Pullulan

Abstract: This paper proposes a convenient route to oxidize the –CH2–OH groups in the water-soluble pullulan, using a new catalytic polymer-supported N-hydroxyphthalimide (NHPI) immobilized on polystyrene. The protocol involves the presence of sodium hypochlorite and sodium bromide. The conversion is possible at room temperature, atmospheric pressure, and pH = 10. The characterization of both the catalysts and oxidized pullulan was done using NMR and FTIR methods. Using polyelectrolyte titration with end-point indicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…NaOH converts the pullulan OH groups into alcoholates, which react via a nucleophilic substitution with the epoxide ring and, thus, facilitate the grafting of the hydrophobic alkyl chain [2-(butoxymethyl)oxirane] to the polysaccharide chain [ 38 ]. According to the literature, the attachment of the hydrophobic alkyl chain is expected to mainly take place at the C 6 primary OH group, owing to its high reactivity and reduced steric hindrance [ 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NaOH converts the pullulan OH groups into alcoholates, which react via a nucleophilic substitution with the epoxide ring and, thus, facilitate the grafting of the hydrophobic alkyl chain [2-(butoxymethyl)oxirane] to the polysaccharide chain [ 38 ]. According to the literature, the attachment of the hydrophobic alkyl chain is expected to mainly take place at the C 6 primary OH group, owing to its high reactivity and reduced steric hindrance [ 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 13 C-NMR spectrum of the BMO reagent is recorded in Figure S1, Supplementary Materials . Other significant peaks in the 13 C-NMR spectrum were depicted as follows: δ = 101–103 ppm for polysaccharide C 1, δ = 68–77 ppm for C 2,3,5 , δ = 80 ppm for C 4 , and δ = 61 ppm for C 6 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Li et al (2021) found that carbon microspheres supported NHPI had good catalytic performances on a variety of alcohols in acetic acid and could be recovered through ltration for recycling. Culica et al (2019) used polystyrene to immobilize NHPI for selective oxidation of pullulan. The oxidized pullulan containing carboxyl groups was obtained, and four oxidation cycles were realized.…”
Section: Introductionmentioning
confidence: 99%
“…In the last stage of the synthesis, catalytically active NHPI moieties were obtained in the reaction with hydroxylamine hydrochloride. A NHPI precursor was similarly deposited on commer-cial polystyrene resins (i.e., aminomethyl and chloromethyl), as well as chloromethylated copolymer of styrene and divinylbenzene [28].…”
Section: Introductionmentioning
confidence: 99%